2011
DOI: 10.1097/mcg.0b013e3181e04d3c
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molecular Imaging to Differentiate Liver Metastasis of Colorectal Cancer Metastasis From Neuroendocrine Tumor Origin

Abstract: Synchronous malignant neoplasms in a single patient are well documented in the literature. It is also recognized that there is increasing incidence of synchronous non-neuroendocrine neoplasm in patients with neuroendocrine tumor (NET). We present a case, of a patient with synchronous colorectal cancer and pancreatic NET, both cancers presenting with liver metastasis. By using 18F-FDG PET and 68Ga-DOTATATE PET imaging, we showed 2 different tumor types within the liver, which was subsequently confirmed on liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…However no sufficient data are available about the role of 68 Ga-SST-analogues PET/CT in this clinical setting [80, 81]. Desai et al [81] reported the usefulness of molecular imaging using different PET radiotracers in order to understand NET biology and subsequently to determine the best treatment option. In this case a different tumor pattern of [ 18 F]FDG and 68 Ga-DOTATATE uptake was shown by PET examinations within the liver, resulting in synchronous colorectal cancer and pancreatic NET liver metastases.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…However no sufficient data are available about the role of 68 Ga-SST-analogues PET/CT in this clinical setting [80, 81]. Desai et al [81] reported the usefulness of molecular imaging using different PET radiotracers in order to understand NET biology and subsequently to determine the best treatment option. In this case a different tumor pattern of [ 18 F]FDG and 68 Ga-DOTATATE uptake was shown by PET examinations within the liver, resulting in synchronous colorectal cancer and pancreatic NET liver metastases.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…This case suggested that combinational 68 Ga-DOTATATE PET and 18 F-FDG PET imaging modalities are of potential use in understanding the biology of the NETs and managing the NETs [38]. …”
Section: The Clinical Use Of Radioisotope Labeled Sstr In Netsmentioning
confidence: 99%
“…2). Indeed, Desai et al [44] reported an interesting case in which molecular imaging was used to differentiate hepatic metastases originating from colorectal cancer and hepatic metastases originating from an NET in the same patient. An 18 F-FDG PET is therefore recommended for NET patients who develop new indeterminate tumor lesions with cross-sectional imaging whenever there is a past medical history of a second malignancy or when a second primary is suspected (level of evidence 4, grade of recommendation C).…”
Section: Recommendations For Specific Clinical Scenariosmentioning
confidence: 99%